Ordinance No. 6, in The Fresno Weekly Republican, November 7, 1885, at 3 - (:unkn) unknown (My University, 1885)
Prohibited the discharge of firearms within the corporate limits of the city. Violators guilty of a misdemeanor. Also prohibited the concealed carry of any pistol, firearm, slung-shot, dirk, Bowie-knife, or other deadly weapon.
Keywords: CARRY - CONCEALED; DISCHARGE